Optimization and storage study of garlic (Allium sativum) incorporated herbal multi-millet sev snack - Tarun Verma; Priya Dey; Ankur Aggarwal; Rajshree Devpal; Rohit Sharma (Food Chemistry Advances, 2023)
The food market is being driven by rising demand for healthy, clean-label, and convenient snacks with improved nutrition profiles, enhanced flavor, and texture, and contains natural ingredients. We developed ‘Herbal Multi-Millet Sev’ with the admixture of the flours of Bengal gram (BG), Finger millet (FM), and Pearl millet (PM) along with the incorporation of Garlic paste (GP). The study was conducted using the different variables of the BG (70-80%), FM (10-20%), PM (10-20%), and GP (5-12%). In order to determine the optimum level of various ingredients for ‘Herbal Multi-Millet Sev’, Response Surface Methodology (RSM) with the central composite rotary design was used for the sensory and textural attributes. The optimized Sev snack sample (maximum desirability∼ 0.963) contains 80g BG flour, 10g FM, and 10g PM flour mixed with 10% GP with a high score overall acceptability and textural profile. The shelf life of the optimized product is more than 200 days of storage by packaging the product in Aluminium laminated polyethylene (50μm thickness) with nitrogen gas flushing; slight microbial growth was observed during this period. Therefore, the underutilized millets may be used for the development of more nutritious and healthier herbal snack foods along with the beneficial effect of garlic.